Immunoendocrinology: Scientific and Clinical Aspects - Eisenbarth, George S.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2011)
Immunoendocrinology is a rapidly developing field of research that seeks to understand the intersection of the immune and endocrine systems. Immunoendocrinology: Scientific and Clinical Aspects explores in detail the current knowledge of immunoendocrinology, namely endocrine disorders produced by disorders of immune function. Chapters cover both basic pathophysiology informed by studies of animal models as well as current understanding of multiple related clinical diseases$1 (Btheir pathophysiology, diagnosis, and therapy. Immunoendocrinology: Scientific and Clinical Aspects captures the central role of immunoendocrinologic processes in the pathogenesis of not only type 1 diabetes but in a range of other autoimmune and endocrine disorders.s
Primer on Immunology Related to Autoimmunity -- Discovering Novel Autoantigens -- Developing and Validating High Sensitivity/Specificity Autoantibody Assays -- Characterizing T Cell Autoimmunity -- Inflammation/Metabolic Syndrome -- Animal -- APS-I Man -- IPEX -- APS-2 -- Iatrogenic immunoendocrinopathy -- BB rat -- Immunopathogenesis of the NOD mouse -- KRV and Related Models Type 1 Diabetes -- Autoimmune Pathology of Type 1 Diabetes -- Genetics -- Epidemiology -- Natural History -- Immunotherapy -- LADA -- Fulminant Diabetes -- Insulin Autoimmunity -- Lessons from Patients with Anti-Insulin Receptor Autoantibodies -- Transplantation -- Addison$1 (Bs Disease -- Animal Models of Autoimmune Thyroid Disease -- Genetics of Thyroid Autoimmunity -- Thyroiditis -- Graves$1 (BDisease -- Graves$1 (BOphthalmopathy -- Hypoparathyroidism -- Gonadal Failure -- Celiac Disease and Intestinal Endocrine Autoimmunity -- Hypophysitis.s
Keywords: Medicine; Immunology; Internal medicine; Endocrinology; Medicine & Public Health; Endocrinology; Immunology; Internal Medicine